2001
DOI: 10.4049/jimmunol.166.12.7362
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Roles of LFA-1 and Mac-1 in Host Defense Against Systemic Infection with Streptococcus pneumoniae

Abstract: Mice deficient in CD18, which lack all four CD11 integrins, have leukocytosis and increased susceptibility to bacterial infection. To determine the effect of deficiencies in LFA-1 (CD11a/CD18) or Mac-1 (CD11b/CD18) on host defense against systemic bacterial infection, knockout mice were inoculated i.p. with Streptococcus pneumoniae. Increased mortality occurred in both LFA-1−/− (15 of 17 vs 13 of 35 in wild type (WT), p < 0.01) and Mac-1−/− (17 of 34 vs 6 of 25, p < 0.01) mice. All deaths in LFA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…CD18 Ϫ/Ϫ mice lack CR3 and CR4 and have lower expression of CR1/2, which tends to make them more susceptible. In contrast, these mice are predicted to have neutrophilia associated with their lack of LFA-1 (33,34), and we showed that they express elevated levels of anti-pneumococcal Abs. We propose that in CD18 Ϫ/Ϫ mice, the combined benefits of neutrophilia and high protective Ab titers overcomes the detrimental effects of low CR1/2 expression and the absence of CR3 and CR4.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…CD18 Ϫ/Ϫ mice lack CR3 and CR4 and have lower expression of CR1/2, which tends to make them more susceptible. In contrast, these mice are predicted to have neutrophilia associated with their lack of LFA-1 (33,34), and we showed that they express elevated levels of anti-pneumococcal Abs. We propose that in CD18 Ϫ/Ϫ mice, the combined benefits of neutrophilia and high protective Ab titers overcomes the detrimental effects of low CR1/2 expression and the absence of CR3 and CR4.…”
Section: Discussionmentioning
confidence: 66%
“…experiment a serotype 6 pneumococcal strain was used (34), whereas we used a serotype 3 strain. Notably, LFA-1 Ϫ/Ϫ animals reportedly have a higher number of neutrophils in the peripheral blood than WT (33,34), which could also account for their improved resistance to i.v. infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LFA-1-deficient mice have deficits in experimental tumor models and increased mortality to gram (ϩ) sepsis with Streptococcus pneumoniae, they exist without apparent spontaneous illness in conventional mouse housing facilities (45,46). Our findings portend several therapeutic implications.…”
Section: Discussionmentioning
confidence: 79%
“…CD11b is also important for innate immune/host defense responses in that loss of CD11b significantly impairs resistance against bacterial challenge. 54,55 Moreover, it has been reported that the severity of DSS colitis is influenced by enteric bacterial; therefore, it could be that genetic loss of CD11b is permissive for bacterial translocation from the colon thereby enhancing disease. 56,57 Blood and mesenteric lymph node cultures from all of the genetic variants in this study were not different from one another, suggesting that bacterial burden is not a mitigating factor for enhanced disease activity in CD11b null mice.…”
Section: Discussionmentioning
confidence: 99%